Primordial germ cells as a potential model for understanding (Nutri) epigenetic - metabolic interactions: a mini review - Ibrahim, Mariam; Grochowska, Ewa; Stadnicka, Katarzyna (Frontiers in Cell and Developmental Biology, 2025)
Primordial germ cells (PGCs) are the progenitors of gametes (sperm and eggs), making them crucial for understanding germline transmission and epigenetic modifications, which are critical for studying transgenerational effects of nutrition and metabolic diseases. This is particularly relevant given the growing evidence that environmental factors, such as diet, can influence metabolic disease risk across generations through modulating epigenetic mechanisms, as seen in both human and animal studies. The unique biological and experimental attributes make PGCs in the chicken embryo a potential model for exploring the complex interactions between nutrition, epigenetic inheritance, and metabolic diseases, providing insights that are translatable to metabolic health and disease prevention tactics. This brief review emphasizes the potential of chicken PGCs as a model system to investigate the mechanisms underlying transgenerational metabolic programming.